Productivity and saving channels of economic growth as latent variables: an application of confirmatory factor analysis - Bebczuk, Ricardo (Estudios de Economía, 2016)
When it comes to measure the sources of growth and draw economic policy conclusions, economists rely on growth accounting. According to this approach, per capita growth is explained by two sources: capital accumulation and total factor productivity. Our contention is that growth accounting suffers from serious pitfalls once we take into account that: (i) Total factor productivity and investment are not independent of each other, and (ii) Total factor productivity is badly measured. The result is that the sources of growth are directly unob-servable, undermining any conclusion based on available measures. To partially overcome these problems, we introduce a technique especially designed to deal with unobservable, or latent variables, called confirmatory factor analysis. We examine both the relationship between fourteen variables correlated to the growth rate and two latent variables: the “savings channel” and the “productivity channel”, and the correlation between the latter.